Editorial for “Materials Chemistry” Section, in Journal Molecules - Giulio Malucelli (Molecules, 2020)
Dear colleagues and friends, it is a great pleasure to summarize the most significant successes achieved during 2019 in the “Materials Chemistry” Section (https://www [...]